Determinants of customer behavioural responses: A pilot study - Maiyaki, Ahmed Audu; Mohd Mokhtar, Sany Sanuri (Canadian Center of Science and Education (CCSE), 2011)
The paper aims at exploring a small sample data on the determinants of customer behavioural responses in the Nigerian retail banking. Hence, instrument validity, reliability and subsequently the data normality were examined through panel of expert and also by analysing small sample data with aid of SPSS software. Results show that the instrument is reliable and the data for preliminary study exhibit reasonable normality.The research explored and validated the instrument of the various antecedents of consumer behavioural responses most of which were hitherto ignored.